Kinerja Layanan Penumpang Angkutan Bus Trans Lampung Rute Bandar Lampung - Bandara Raden Inten II - Afrisca, Cahya Ayu; Sulistyorini, Rahayu; Putra, Sasana (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2019)
Raden Inten II Airport has been designated as an international airport under the Decree of the Minister of Transportation of the Republic of Indonesia Number KP 2044 of 2018 (Baraas, 2015). With the rate of growth of the population in Lampung Province which continues to increase and the number of aircraft passengers at RadenInten II Airport continues to increase every year. So the service of land transportation in Raden Inten II Airport becomes the choice of passengers as an advanced transportation to end the trip, so that the community always demands quality public service.The purpose of this study was to find out and analyze the Performance of Passenger Trans Lampung Bus Transport Services at Bandar Lampung Department – Raden Inten II Airport which was measured based on Load Factor, Time Headway, Cycle Time and Travel Speed.In this study, the average speed obtained on Saturday Sunday and Monday on the departing route is 31.35 km / hour and on the return route is 29 km / hour. For the average value of Load Factor on the departing route (Bandar Lampung-Airport) by 15% and the average Load Factor on the return route (Bandar Lampung Airport) by 30%. Time Headway obtained an average value of calculations of 60.1 minutes and the value of Cycle Time 2 hours 53 minutes.Keywords: load factor, time headway, speed, bus service performance.